HIV care in times of the COVID-19 crisis — Where are we now in Central and Eastern Europe?. (July 2020) - Kowalska, J.D.; Skrzat-Klapaczyńska, A.; Bursa, D.; Balayan, T.; Begovac, J.; Chkhartishvili, N.; Gokengin, D.; Harxhi, A.; Jilich, D.; Jevtovic, D.; Kase, K.; Lakatos, B.; et al.
Abstract: Introduction: The SARS-CoV-2 pandemic has hit the European region disproportionately. Many HIV clinics share staff and logistics with infectious disease facilities, which are now on the frontline in tackling COVID-19. Therefore, this study investigated the impact of the current pandemic situation on HIV care and continuity of antiretroviral treatment (ART) supplies in CEE countries. Methods: The Euroguidelines in Central and Eastern Europe (ECEE) Network Group was established in February 2016 to review standards of care for HIV in the region. The group consists of professionals actively involved in HIV care. On March 19, 2020 we decided to review the status of HIV care sustainability in the face of the emerging SARS-CoV-2 pandemic in Europe. For this purpose, we constructed an online survey consisting of 23 questions. Respondents were recruited from ECEE members in 22 countries, based on their involvement in HIV care, and contacted via email. Results: In total, 19 countries responded: Albania, Armenia, Belarus, Bosnia and Herzegovina, Bulgaria, Croatia, Czech Republic, Estonia, Georgia, Greece, Hungary, Lithuania, Macedonia, Poland, Republic of Moldova, Russia, Serbia, Turkey, and Ukraine. Most of the respondents were infectious disease physicians directly involved in HIV care (17/19). No country reported HIV clinic closures. HIV clinics were operating normally in only six countries (31.6%). In 11 countries (57.9%) physicians were sharing HIV and COVID-19 care duties. None of the countries expected shortage of ART in the following 2 weeks; however, five physicians expressed uncertainty about the following 2 months. At the time of providing responses, ten countries (52.6%) had HIV-positive persons under quarantine. Conclusions: A shortage of resources is evident, with an impact on HIV care inevitable. We need to prepare to operate with minimal medical resources, with the aim of securing constant supplies of ART. Non-governmental organizations should re-evaluate their earlier objectives and support efforts to ensure continuity of ART delivery.